An Experimental Validation of Sequential Multiple-Choice Tests. Issue 2 (3rd April 2021) - Papenberg, Martin; Diedenhofen, Birk; Musch, Jochen
Abstract: Testwiseness may introduce construct-irrelevant variance to multiple-choice test scores. Presenting response options sequentially has been proposed as a potential solution to this problem. In an experimental validation, we determined the psychometric properties of a test based on the sequential presentation of response options. We created a strong validity criterion by providing participants with different levels of information on a domain about which they had no prior knowledge. Test takers' capability of guessing the correct answer was strongly reduced by the sequential test format, whereas sequential test scores were as valid and reliable as multiple-choice test scores. We concluded that the sequential presentation of response options should be investigated more closely as a viable alternative to the traditional multiple-choice test format.